Forensic Implications of Anatomical Education and Surgical Training With Cadavers - Pirri, Carmelo; Stecco, Carla; Porzionato, Andrea; Boscolo-Berto, Rafael; Fortelny, René H.; Macchi, Veronica; Konschake, Marko; Merigliano, Stefano; De Caro, Raffaele (Frontiers in Surgery, 2021)
Anatomical education and surgical training with cadavers are usually considered an appropriate method of teaching, above all for all surgeons at various levels. Indeed, in such a way they put into practice and exercise a procedure before performing it live, reducing the learning curve in a safe environment and the risks for the patients. Really, up to now it isn’t clear if the non-use of the cadavers for anatomical education and surgical training can have also forensic implications. A substantial literature research was used for this review, based on PubMed and Web of Science database. From this review, it is clear that the cadaveric training could be considered mandatory, both for surgeons and medical students, leading to a series of questions with forensic implications. Indeed, there are many evidences that a cadaver-lab can improve the learning curve of a surgeon, above all in the first part of the curve, in which frequent and severe complications are possible. Consequently, a medical responsibility for residents and surgeons which perform a procedure without adequate training could be advise, but also for hospital, that has to guarantee a sufficient training for its surgeons and other specialists through cadaver-labs. Surely, this type of training could help to improve the practical skills of surgeons working in small hospitals, where some procedures are rare. Cadaver studies can permit a better evaluation of safety and efficacy of new surgical devices by surgeons, avoiding using patients as «guinea pigs». Indeed, a legal responsibility for a surgeon and other specialists could exist in the use of a new device without an apparent regulatory oversight. Good medical practice requires the surgeon to inform the patient of any uncertainty regarding risks associated with the procedure, ensure that the patient fully understands that the procedure is new and that they have used the technique on few, if any, patients before. Cadaver training could represent a shortcut in the standard training process, increasing both the surgeon learning curve and patient confidence. Forensic clinical anatomy can supervise and support all these aspects of the formation and of the use of cadaver training.